Operational gaming : an international approach - Stahl, Ingolf, 1940- (Frontiers of operational research and applied systems analysis ;, 1983)
Operational Gaming: An International Approach focuses on various research on this method of systems analysis. The text points out the value of this method in decision making, planning, and in the implementation of policies. The book presents a survey that highlights the connection of experimental gaming, game theory, and operational gaming. The value of gaming as a balancing method in assessing multifaceted computer models, most notably about their assumptions on human behavior, is noted. The book also offers an overview of gaming in other countries, such as Bulgaria, Soviet Union, and Japan,